Soviets et salaires : les sardinières dans la grève de Douarnenez (novembre 1924-janvier 1925) - Théo Bernard (Cahiers d’histoire.)
At the end of November 1924, a strike broke out among the women of the Douarnenez canning industry in Finistère. Mobilizing 2200 workers, the strike lasted seven weeks and challenged, for a brief period, the power and authority of the bosses, the state and even the Communist militants at the head of the Douarnenez town hall and in the position of union intermediaries in the strike. During the conflict, the demands, the place of women, the sovereignty of the plenary assemblies of strikers, the prerogatives of the strike committee controlling the productive activity of the port, the form of the demonstrations and the road blockades all expressed the depth of the revolt. The effectiveness of the workers' participation in the direction of the movement contributes to define the nature of the conflict whose political dimensions were combined with a conscious organization of the strike.